1994
DOI: 10.1007/bf01222246
|View full text |Cite
|
Sign up to set email alerts
|

Adenosquamous carcinoma of the liver: case report

Abstract: We report a case of adenosquamous carcinoma of the liver arising from the left intrahepatic bile duct. A 65year-old man was referred to our hospital with epigastric discomfort of 2 weeks' duration. The results of laboratory and clinical investigations suggested the presence of a cholangiocarcinoma; consequently, left hepatectomy with caudate lobectomy were performed. The histopathological examination revealed adenocarcinoma, squamous carcinoma, and transitional cancer cells in the resected specimen. Multiple l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…1,2,[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] The preoperative diagnosis was extremely difficult, with only three patients correctly diagnosed by aspiration cytology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2,[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] The preoperative diagnosis was extremely difficult, with only three patients correctly diagnosed by aspiration cytology.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical experience with ASC of the liver has been previously reported, and it has been reported that the main initial symptoms were abdominal pain, abdominal discomfort, fever, and jaundice (Table 1). 1,2,[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] The preoperative diagnosis was extremely difficult, with only three patients correctly diagnosed by aspiration cytology.…”
Section: Discussionmentioning
confidence: 99%
“…A tumor with both adenocarcinoma and squamous cell carcinoma components has previously been referred to as mucoepidermoid carcinoma, 1–6 adenoacanthoma 7 and adenosquamous carcinoma 8–27 . It sometimes develops in the digestive tract, pancreas, gallbladder and thyroid, but rarely in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…A tumor with both adenocarcinoma and squamous cell carcinoma components has previously been referred to as mucoepidermoid carcinoma, 1-6 adenoacanthoma 7 and adenosquamous carcinoma. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] It sometimes develops in the digestive tract, pancreas, gallbladder and thyroid, but rarely in the liver. Adenosquamous carcinoma of the liver is a special type of intrahepatic cholangiocarcinoma that develops from the biliary epithelial lining cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation